Praktik Jual Beli Ikan Asin Ditinjau Dari Fiqh Muamalah - Ahmatnijar, Hendri JP Siregar Syafri Gunawan & (Jurnal El-Thawalib, 2020)
Salted Fish is a kitchen food ingredient. In the Hajoran Indah sub-district, there are sellers who sell salted fish by mixing the wet and dry ones in one basket. The problem in this case is how the practice of buying and selling salted fish in Hajoran Indah sub-district and how the muamalah fiqh review of the practice of buying and selling salted fish in Hajoran Indah sub-district Pandan district, Central Tapanuli district. This type of research used in this research is field research (field research). Based on the results of this study, it was found that the practice of buying and selling salted fish in Hajoran Indah village is like buying and selling in general. However, the seller in conducting the transaction did not explain purely the condition of the salted fish in the basket, the buyer could only see the top part. Overall, the sale and purchase of mixing wet and dry salted fish in one container is legal, as long as the sale and purchase transaction between the seller and the buyer is honest by telling the truth, it is clear that the quality of salted fish being sold is mixing, then the law of buying and selling is is legal. However, when the seller behaves dishonestly that the salted fish has been mixed with salted fish which is still wet, it will result in defects, so the sale and purchase is declared invalid.